Reform in Canadian Universities - Small, J. M. (Canadian Journal of Higher Education, 1994)
This article reports a survey of academic vice-presidents and deans of Canadian universities which was undertaken in 1991. The focal topic was reform (defined as significant change), and perceptions of reform occurring over the past three years were derived by means of a questionnaire. Many changes were reported, giving the impression of highly responsive institutions, but these reforms were seen to be modest rather than bold in nature and reactive rather than pro-active. The major environmental influence impelling change was the level of funding. The reforms perceived to be most frequent and significant were mandate changes arising from strategic planning, responses to funding constraints, curriculum expansion, coping with increased student numbers, changes in administrative structure especially at the vice-presidency, and more democratic decision-making. Respondents were generally supportive of the goals which were perceived to lie behind the reforms but were not convinced that significant progress towards goals was actually being achieved. A comparison with reform in other parts of the world revealed that Canadian universities follow the decentralized ad hoc pattern found in federal nations, but there is reason to hope that strategic planning will produce a clearer sense of direction than has been typical elsewhere. The report concludes that the claim that universities are not responsive to changing societal needs is unwarranted, but that more significant lasting reforms are needed.